Obliczanie masy wody towarzyszącej przy drganiach poprzecznych silników okrętowych - WIĘCKOWSKI, Józef (Engineering Transactions, 1957)
Computation of the added mass of water during transverse vibration of a marine engine Based on the equations of plane potential flow of an ideal liquid, a computation. is made surface density of the apparent added mass of water during transverse vibration of a marine engine, assuming infinitely high frequency of water particles and disregarding the influence of free waves. A numerical example illustrates the calculations for an elliptical contour, assuming the values of the geometrical and mechanical parameters characterizing the contour from real steel ,cutters. A comparison of the values obtained for the density of the added mass of water, with approximate values according to O. Grimm, [1], has shown the necessity of accurate calculation. Finally, problems connected with transverse vibrations of engines are discussed in the light of the results of vibration measurements, [8], for steel cutters.